A study on website quality and its impact on customer satisfaction with reference to ecommerce companies - KRISHNAMOORTHY, D.; VIGRAM, R.P. (The journal of contemporary issues in business and government, 2020)
Online shopping is a form of electronic commerce which allows consumers to directly buy goods or services from a seller over the Internet using a web browser. Consumers find a product of interest by visiting the website of the retailer directly or by searching among alternative vendors using a shopping search engine, which displays the same product's availability and pricing at different e-retailers. As of 2020, customers can shop online using a range of different computers and devices, including desktop computers, laptops, tablet computers and smartphones. An online shop evokes the physical analogy of buying products or services at a regular "bricks-and-mortar" retailer or shopping center; the process is called business-to-consumer (B2C) online shopping. When an online store is set up to enable businesses to buy from another businesses, the process is called business-to-business (B2B) online shopping. This Study explains how the customer gets satisfied with the quality of online shopping websites. we collected various response from 201 respondents based on the satisfaction with website quality of ecommerce websites.